Potential Impact of Late 1980s Regime Shift on the Collapse of Walleye Pollock Catch in the Western East/Japan Sea - Kim, Yong-Yub; Kang, Yu-Kyeong; Lee, Seung-Tae; Jung, Hae Kun; Lee, Chung Il; Kim, Sangil; Jeong, Kwang Young; Byun, Do-Seong; Cho, Yang-Ki (Frontiers in Marine Science, 2022)
Walleye pollock (Gadus chalcogramma) caught in the Korean fishing area dramatically decreased in the late 1980s. To investigate the potential impact of the late 1980s climate regime shift on the collapse of the pollock catch, we developed a three-dimensional hydrodynamic model with data assimilation and a particle tracking model. Data-assimilated reanalysis showed that sea surface temperature increased by approximately 2 °C in the spawning area of pollock in the late 1980s. The suitable spawning area in the East Korean Bay decreased due to warming in the late 1980s. Spawned eggs of walleye pollock were tracked using a particle tracking model for 30 days in January and February during 1983–1992. The number of individuals transported to the nursery within the Korean fishing area from the spawning area was reduced by 74 % in the late 1980s. The intensified East Korean Warm Current (EKWC) could be responsible for the decreased number of individuals transported to the southern area in the late 1980s. Warming in the Korean fishing area could also cause a decrease in pollock. These oceanic changes might be linked to climate regime shifts in the late 1980s. The warming regime with positive Arctic Oscillation and weakened monsoon intensified the northward flow of the EKWC and accelerated the warming of the spawning and fishing areas in the late 1980s.